Data for Stencil selection algorithms publication - Tsoutsanis, Panagiotis (Cranfield University, 2019)
Dataset for simulation1) eps images of simulation outputs2) mp4 /mpg of video animation of simulations3) tecplot plt files (use Tecplot, or Paraview for visualisation)
Keywords: WENO; Applied Mathematics not elsewhere classified; Computational Fluid Dynamics